The Effect of Role Conflict and Ethical Sensitivity on Auditor Performance with Moderation of Emotional Intelligence - Elvina Lase; Teng Sauh Hwee; Yusuf Ronny Edward (Journal of Economics, Business, and Accountancy Ventura, 2021)
Auditors are required to be professional to carry out their duties properly in examining the client's financial statements to provide benefits to the client and interested parties on the audit results. However, this professional attitude cannot be separated from the auditor's role conflict and his ability to make ethical decisions. Therefore, this study aimed to examine the effect of role conflict and ethical sensitivity in improving the auditor’s performance using emotional intelligence as a moderating variable. The cluster sampling technique was used to determine the number of samples, as many as 86 auditors at the Medan City Public Accounting Firm. The data was collected using a questionnaire method. Fifty-six auditors were used for hypothesis testing and research analysis, while 30 other auditors were used to determine validity and reliability tests. This study uses a structural equation model to test the hypothesis. The results show that role conflict harms auditor performance, while ethical sensitivity increases auditor performance. On the other hand, emotional intelligence does not mediate the effect of role conflict and ethical sensitivity on auditor performance. The implication of the results of this study is the need for public accounting firms to manage internal competition between auditors so as not to lead to personal conflicts that can decrease audit quality. Public accounting firms also need to develop an ethical culture among their auditors.